A. H. Goodman, D. Heathy M. S. Lindee (eds.). Genetic Nature/Culture. Anthropology and Science beyond the Two-Culture Divide Berkeley, University of California Press, 2003, 318 páginas - Pellegrini, Pablo (2005)
Fil: Pellegrini, Pablo. Universidad Nacional de Quilmes; Argentina.